Helminth eggs inactivation efficiency by faecal sludge dewatering and co-composting in tropical climates - Koné, D.; Cofie, Olufunke O.; Zurbrugg, C.; Gallizzi, K.; Moser, D.; Drescher, S.; Strauss, M. (2007)
This study investigates helminth eggs removal and inactivation efficiency in a treatment process combining faecal sludge (FS) dewatering and subsequent co-composting with organic solid waste as a function of windrow turning frequency. Fresh public toilet sludge and septage mixed at a 1:2 ratio were dewatered on a drying bed. Biosolids with initial loads of 25-83 helminth eggs/g total solids (TS) were mixed with solid waste as bulking material for co-composting at a 1:2 volume ratio. Two replicate sets of compost heaps were mounted in parallel and turned at different frequencies during the active composting period: (i) once every 3 days and (ii) once every 10 days. Turning frequency had no effect on helminth eggs removal efficiency. In both setups, helminth eggs were reduced to o1 viable egg/g TS, thereby complying with the WHO guidelines 2006 for the safe reuse of FS.